Comparison of intravenous butorphanol vs. tramadol for post-spinal anesthesia shivering: a meta-analysis and systematic review - Wan, Ji-Xiang; Li, Xue-Chao; Zeng, Si-Si; Li, Yu-Qian; Wang, Fang-Jun (Frontiers in Medicine, 2023)
Background Patients often experience shivering after spinal anesthesia. In recent years, more and more studies have compared the efficacy and side effects of intravenous butorphanol and tramadol in the treatment of shivering after spinal anesthesia. Therefore, we conducted a MATE analysis and systematic review to compare the efficacy and side effects of butorphanol vs. tramadol in the treatment of shivering after spinal anesthesia. Methods PubMed, Cochrane Library, and Embase databases were searched for randomized controlled trials (RCTs) from inception to 30 December 2022, comparing the effects of butorphanol vs. tramadol for the control of shivering after spinal anesthesia. Data assessment and collection were analyzed using the Review Manager 5.4 software. Results Five randomized controlled trials involving 302 adult patients were included in this meta-analysis. The results showed that butorphanol has a shorter time to cease shivering (standardized mean difference (SMD) = −0.53; 95% confidence interval (CI) [−0.89, −0.17], P = 0.004, I2 = 0%), a higher rate of cessation of shivering within 1 min after administering the study drugs (relative risk (RR), 1.69; 95% CI [1.15,2.48], P = 0.008, I2 = 0%), and higher incidences of sedation (RR, 2.98; 95% CI [2.11, 4.21], P <0.00001, I2 = 0%), compared with tramadol. Conclusion In the treatment of shivering after spinal anesthesia, butorphanol has a shorter onset time and a higher rate of cessation of shivering within 1 min after the study drugs were administered than tramadol. Therefore, butorphanol is superior to tramadol in the treatment of shivering after spinal anesthesia.